The screening of local herbs in treating non healing wounds and diabetic foot ulcers complications using nih 3t3 mouse fibroblast and raw 264.7 mouse macrophage cells - Wan Sulaiman, Wan Mohd Azizi; N.K., Sunzida; A. K., Azad (SILAE (Italo-Latin American Society of Ethnomedicine), 2016)
Lee Indica and Stachytarpeta is the common plant in Malaysia and people are using as a traditional wound healing agent since an ancient era. The aim of this current study was to determine the diabetic wound healing activity. The NIH 3T3 mouse fibroblast cells and RAW 264.7 mouse macrophage cells cultured to confluence in a six-well culture plate, and the culture medium drained away. The area of cell is scraped gently with a rubber stick to create a wound with 0.5mm width. The herbal extract added at 100 mg/mL to the culture while the control culture received only PBS. The migration of cells were observed after 24 h. The leea indica and stachytarpeta indica has shown a positive results when tested on RAW macrophage cells compared to its result when tested on NIH 3T3 mouse fibroblast cells which shows a less positive results. It can be concluded that both leea indica and stachytarpeta indica can be used to treat wound as it enhance the mitochondrial activities of cells. The extract from leea indica is more effective on tested cells compare than stachytarpeta indica. It is suitable to be used on macrophage cells rather than on fibroblast cells. It will support to the use of leea indica for the treatment of wound healing.